Outcomes Following Stereotactic Body Radiotherapy with Intensity-Modulated Therapy versus Three-Dimensional Conformal Radiotherapy in Early Stage Non-Small Cell Lung Cancer - Mix, Michael (Lung Cancer (Auckl), 2019)
INTRODUCTION: The treatment techniques used for stereotactic body radiation therapy (SBRT) for early-stage lung cancer continue to evolve. In this study, clinical outcomes following SBRT were evaluated according to the use of either 3D conformal radiotherapy (3DCRT) or intensity-modulated radiation therapy (IMRT). PATIENTS AND METHODS: Patients with stage I NSCLC who received SBRT from 2007 to 2015 were retrospectively reviewed. Disease control and survival were assessed using Kaplan-Meier estimates. Dosimetric analyses for target dose heterogeneity and coverage were performed. RESULTS: A total of 297 patients with 351 lesions were included. 3DCRT was used in 52% and IMRT in 48%. IMRT was utilized at a higher rate in more recent years. The most common regimens were 48 Gy in 4 fractions and 54–60 Gy in 3 fractions. With a median follow up of 22.7 months, there were 17 local failures for a crude relapse rate of 5.7%. Local failure did not differ in patients treated with 3DCRT and IMRT (4.9% vs 6.5%, p=0.573). Mean dose to gross tumor volume (GTV) as a percent of prescription dose was higher with 3DCRT compared with IMRT (107.7% vs 103.6%, p < 0.0001). Tumor stage, histology, and SBRT regimen did not correlate with local tumor control. Overall survival for the entire population approximated 72% at 2 years. Treatment was well tolerated with 6 documented grade 3+ events. CONCLUSION: In this single-institution cohort of SBRT for early-stage NSCLC, there was no discernible difference in clinical outcomes between those treated with 3DCRT and IMRT.